Justice and Constructivism. (May 2015) - Matravers, Matt
Albert Weale's Democratic Justice and the Social Contract is an important book. It offers an innovative and original (proceduralist) account of justice. In so doing, it places what Brian Barry called 'the empirical method' at the centre of normative political philosophy's attempts to generate determinate answers to moral questions. This article-written from the perspective of someone sympathetic to both the commitment to mutual advantage and the empirical method – focuses on the kind of argument it is that Weale is offering and in particular on the nature of his constructivist project. It argues that Weale's commitment to equality lies outside the constructivist project and that this undermines his aspiration to genuine constructivism. The article goes on to consider, on the basis of arguments found in Democratic Justice and the Social Contract, various ways in which Weale might have grounded his egalitarian commitments from within the constructivist project.